The Myth of Lycurgus in Aeschylus, Naevius, and beyond - Bednarek, Bartłomiej, (Mnemosyne, Supplements ;, 2021)
Lycurgus, the king of the Thracian tribe of the Edonians, is the hero of the first attested Greek myth about the resistance against the god Dionysus. According to many scholars, Lycurgus was worshipped as a god among the Thracians, Phrygians, and Syrians. His myth might have been used as a hieros logos in the initiations into the 'Bacchic' and 'Orphic' mysteries in Greece and Rome. This book focuses on Aeschylus' tragic tetralogy Lycurgeia and Naevius' tragedy Lycurgus , the two most important texts that shaped the tradition of the Lycurgus myth, and offers a new and, at times, radically different interpretation of these fragmentary plays and related cultural texts.